TINJAUAN YURIDIS PEMBATALAN PUTUSAN ARBITRASE BERDASARKAN PASAL 70 UNDANG-UNDANG NOMOR 30 TAHUN 1999 ANTARA PELAKU USAHA YAITU PT. CAHAYABARU RAYA REALTY DENGAN KONSUMEN YAITU DAVID WIRYANTO - Erika Michelle Angel; Gindo L. Tobing; Wiwik Sri Widiarty (Fakultas Hukum Universitas Kristen Indonesia, 2021)
Based on the Regulation of the Supreme Court of the Republic of Indonesia Number 1 of 2006, business actors and consumers are given the right to freedom if they want to reject or submit objections in accordance with the provisions of the prevailing laws and regulations. In this case, the consumer submits a complaint to the South Tangerang Consumer Dispute Resolution Agency through arbitration. After the arbitration award is available, the parties do not find a settlement agreement in the Consumer Dispute Resolution Board, the request for annulment of the arbitration award is final and binding but not in this case. In this case, the business actor will file an appeal to the district court against the cancellation of the arbitration award. Keywords : Undang-undang Perlindungan Konsumen, Perlindungan Konsumen (Pembeli), Bisnis (Pengembang), Badan Penyelesaian Sengketa Konsumen (BPSK), Putusan Arbitrase, Pembatalan, Mahkamah Agung